Evaluation of a modified version of the attitudes about mental illness and its treatment instrument : psychometric assessment and attitudes among adolescents in Sweden - Hermann, Veronica; Dahlberg, Anton; Sarkadi, Anna; Hansson, Lars; Karlsson, Ann Christin; Durbeej, Natalie (Nordic Journal of Psychiatry, 2025)
Introduction: Globally, many adolescents suffer from mental health problems and related stigma. Assessing mental health stigma among youth is crucial to addressing this problem. The aim of this study was to examine the psychometric properties of a modified version of the Attitudes About Mental Illness and its Treatment (AAMIT) instrument and to describe attitudes according to the instrument, among Swedish adolescents. Methods: A total of 2,079 adolescents in lower and upper secondary high schools on Gotland, Sweden, responded to the instrument. Exploratory and confirmatory factor analyses and assessment of internal consistency were conducted. The adolescents’ views on the instrument were analysed through qualitative content analysis of open-ended comments. Results: Exploratory factor analysis suggested a three-factor model, with seven items in total. The internal consistency of the subscales was found to be acceptable, with alpha values at 0.72–0.80. Mean scores on the subscales indicated a low prevalence of negative attitudes overall. However, 34.7% of the participants agreed with the stereotype that people with mental health problems are unpredictable, and 25.5% agreed that it is difficult to talk to people with such conditions. Negative attitudes were more prevalent among boys and adolescents with a foreign background. Many participants, nonetheless, found it difficult to evaluate the item statements, and a substantial proportion selected the ‘don’t know’ response option. Conclusion: Findings indicate a need for inclusive mental health education throughout the general population, youth involvement in attitude assessment design, and further validation of the AAMIT instrument before its application in future research.
Keywords: Adolescent; attitude; mental health problems; psychometrics; stigma